Managing and documenting your project XML style some potentially powerful uses for XML technology. - Fisher, Timothy (XML journal :the ultimate enterprise resource.)
XML seems to be popping up everywhere. In this article, I'm going to touch on an often overlooked but potentially very powerful use for XML technology : XML for project management and documentation. Thanks to the open source community, there are some marvelous tools available for incorporating XML into your software development processes.